Reliability Allocation Method for Electric Aircraft Lightweight Propulsion System - LI Jinghao, LI Ran, HUA Hao, HUANG Wentao, GAO Fei, TAI Nengling (Shanghai Jiaotong Daxue xuebao)
In order to solve the contradiction between lightweight and high reliability in the electric aircraft electric propulsion system, a reliability allocation method considering lightweight constraint is proposed for the first time. An analytical expression between weight and reliability is integrated into the electric propulsion system design model as constraints, and a flexible “weight-reliability” optimization method is proposed, considering the uncertainty of the operating conditions of electric aircraft. This method achieves minimum weight under reliability constraints and maximum reliability under weight constraints. Taking the “Spirit of Innovation” electric aircraft as an example, the results show that the proposed method can reduce the total weight of the power system of the electric aircraft by 3.5% while ensuring the reliability of the system. The applicability of the proposed method is verified in different scenarios designed, providing technical support for the development of high power-to-weight ratio in electric aircrafts.